A numerical performance assessment of a commercial cardiopulmonary by-pass blood heat exchanger. Issue 6 (June 2015) - Consolo, Filippo; Fiore, Gianfranco B.; Pelosi, Alessandra; Reggiani, Stefano; Redaelli, Alberto
Highlights: We designed a new blood heat exchanger with ameliorated efficiency and reliability. The numerical-based design strategy eliminated the need of iterative prototyping. We analyzed geometrical-dependent parameters not derivable from empirical methods. A comprehensive evaluation of hemo- and thermo-dynamics performance was provided. Experimental data proved the effectiveness of the developed numerical tool. Abstract: We developed a numerical model, based on multi-physics computational fluid dynamics (CFD) simulations, to assist the design process of a plastic hollow-fiber bundle blood heat exchanger (BHE) integrated within the INSPIRE TM, a blood oxygenator (OXY) for cardiopulmonary by-pass procedures, recently released by Sorin Group Italia. In a comparative study, we analyzed five different geometrical design solutions of the BHE module. Quantitative geometrical-dependent parameters providing a comprehensive evaluation of both the hemo- and thermo-dynamics performance of the device were extracted to identify the best-performing prototypical solution. A convenient design configuration was identified, characterized by (i) a uniform blood flow pattern within the fiber bundle, preventing blood flow shunting and the onset of stagnation/recirculation areas and/or high velocity pathways, (ii) an enhanced blood heating efficiency, and (iii) a reduced blood pressure drop. The selected design configuration was then prototyped and tested to experimentally characterize the device performance. Experimental results confirmed numerical predictions, proving the effectiveness of CFD modeling as a reliable tool for in silico identification of suitable working conditions of blood handling medical devices. Notably, the numerical approach limited the need for extensive prototyping, thus reducing the corresponding machinery costs and time-to-market.